5 Outcomes following ANTI-TNF discontinuation and the risk of relapse in inflammatory bowel disease; a single centre experience. (5th April 2017) - Coffey, L; Mullen, A; Leyden, J; MacMathuna, P
Abstract : Background: Crohn's disease (CD) and Ulcerative Colitis (UC) are chronic inflammatory bowel (IBD) conditions that result in fluctuations of disease activity. Infliximab and Adalimumab are well-established agents associated with inducing and maintaining remission in IBD. Long term use of this agent has an associated risk profile and significant healthcare budget implications. Aims: The aim was to identify patients in remission suitable for discontinuation of anti-TNF therapy and follow their clinical course to identify the patients who maintained a clinical remission Methods: A single centre retrospective of our 1000 IBD patients. We reviewed IBD cohort on Anti TNF therapy. Analysis of colonoscopy findings and patient symptoms at time of discontinuation was performed and subsequent clinical follow following withdrawal of therapy. Results: We identified 65 patients on Infliximab. 37 (57%) have UC and 28 (43%) have CD. Following a mean treatment interval of 41 months Infliximab therapy was discontinued in 19 (29%) patients. Of the discontinuation cohort 11 (58%) patients had UC, 6 (31.5%) had CD 2 (10.5%) were indeterminate colitis. During a follow up of 36 months 18 (95%) remained in clinical remission, while 1 (5%) relapsed. We identified 198 patients on Adalimumab in our cohort for treatment of CD. Of this cohort 3 (1.5%) were discontinued as they were in clinical remission. The follow up for this arm was 50 months. There have been 2 (66%) relapses in this group. Conclusions: Successful remission was achieved in 95% of our Infliximab cohort and 33% of our Adalimumab cohort resulting in fewer hospital admissions, improvement in patient quality of life and decreased healthcare costs that are associated with provision of both maintenance and rescue therapy for flares of disease.